2017
DOI: 10.1093/jb/mvx038
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+/calmodulin-dependent protein kinase II promotes neurodegeneration caused by tau phosphorylated at Ser262/356 in a transgenic Drosophila model of tauopathy

Abstract: Abnormal deposition of the microtubule-associated protein tau is a common pathological feature of multiple neurodegenerative diseases, including Alzheimer's disease (AD), and plays critical roles in their pathogenesis. Disruption of calcium homeostasis and the downstream kinase Ca2+/calmodulin-dependent protein kinase II (CaMKII) coincides with pathological phosphorylation of tau in AD brains. However, it remains unclear whether and how dysregulation of CaMKII affects tau toxicity. Using a Drosophila model, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 52 publications
1
22
0
Order By: Relevance
“…Another study showed that CaMKII dysregulation in Alzheimer’s patients may be a modulator of toxicity in Alzheimer’s disease, a dementia characterized by aberrant calcium signaling, synapse and neuronal loss, and impaired memory 60 . A Different study showed that disruption of calcium homeostasis and the downstream kinase CaMKII coincides with pathological phosphorylation of tau in AD brains 61 .
Fig. 5S-nitrosylation alters the non-canonical Wnt/calcium signaling pathway.Right side: SNO of RYR lead to Ca++ release from the ER.
…”
Section: Discussionmentioning
confidence: 97%
“…Another study showed that CaMKII dysregulation in Alzheimer’s patients may be a modulator of toxicity in Alzheimer’s disease, a dementia characterized by aberrant calcium signaling, synapse and neuronal loss, and impaired memory 60 . A Different study showed that disruption of calcium homeostasis and the downstream kinase CaMKII coincides with pathological phosphorylation of tau in AD brains 61 .
Fig. 5S-nitrosylation alters the non-canonical Wnt/calcium signaling pathway.Right side: SNO of RYR lead to Ca++ release from the ER.
…”
Section: Discussionmentioning
confidence: 97%
“…Although this result is discrepant with many early observations on clinico-phosphorylation status correlation, there is at least one tau phosphorylation site located at residue Thr 205 and recognized by antibody AT8, for which increased stoichiometry of phosphorylation exerts a beneficial/protective effect in the prevention or neutralization of Aβ toxicity [48]. The other potential phospho-acceptor sites typically associated with tau hyperphosphorylation and toxicity include Ser 9 , Ser 26 , Thr 175 , Ser 199 , Thr 231 , Ser 262 , Ser 356 and Ser 396 [4951]. Ser 396 was also increased by TYROBP deficiency, suggesting that multiple competing effects are occurring simultaneously, indicating that the beneficial effects are apparently sufficiently robust to overcome the competing detrimental effects.…”
Section: Discussionmentioning
confidence: 99%
“…CaM is implicated in the regulation of MAPs activity through two complementary mechanisms: firstly, this CBP can control the activity of kinases and phosphatases that act on these cytoskeletal proteins, as exemplified by Ca 2+ /CaM-dependent kinases’ control of tau phosphorylation [160,163,164,165]; secondly, CaM can directly bind to both MAP-2 and tau with a flip-flop mechanism by which CaM binding prevents the association of MAPs and microtubules in a Ca 2+ -dependent manner, thereby destabilizing microtubules [166,167,168]. Interestingly, in the neurons of C. aspersum , both CaM- and P-Tau-like immunoreactivity showed the co-localization of strongly immunopositive masses during hibernation, suggesting a stage-specific interaction that could either be direct or involve the mediation of kinases, which may increase the levels of P-Tau and result in decreased binding to microtubules [133].…”
Section: Cbps In the Hibernating Nervous System: A Role In Neuroprmentioning
confidence: 99%